2022
DOI: 10.1186/s12888-022-04087-8
|View full text |Cite
|
Sign up to set email alerts
|

Previous trauma exposure and self-mastery as moderators of psychiatric effects of home isolation during the Covid-19 pandemic: a field study

Abstract: Background Limiting contagion during the Covid-19 pandemic has necessitated employment of drastic measures ranging from complete lockdown to home isolation and quarantines. This study examined the psychiatric effects of home isolation, the effects of interacting previous traumatic events and the moderating effect of self-mastery as a resilience factor that could mitigate negative effects. Methods Six hundred forty-five adults aged 18–67 completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“… Denerel et al (2022) found that home isolation affected the mental health of athletes, although this effect was weaker compared to non-athletes. Slone et al (2022) found that home isolation caused psychological distress in the public and that the severity of this psychological distress was inversely related to the public’s ability to exercise Self-Mastery (Self-Mastery refers to a sense of having control over life events and is reflected in a self-perception of strength and the capacity to cope with and overcome obstacles by relying on personal efforts). Shechory and Laufer surveyed Israelis living in conflict zones.…”
Section: Introductionmentioning
confidence: 99%
“… Denerel et al (2022) found that home isolation affected the mental health of athletes, although this effect was weaker compared to non-athletes. Slone et al (2022) found that home isolation caused psychological distress in the public and that the severity of this psychological distress was inversely related to the public’s ability to exercise Self-Mastery (Self-Mastery refers to a sense of having control over life events and is reflected in a self-perception of strength and the capacity to cope with and overcome obstacles by relying on personal efforts). Shechory and Laufer surveyed Israelis living in conflict zones.…”
Section: Introductionmentioning
confidence: 99%
“…The patient in this study was quarantined for 10 days after the detection of SARS-CoV-2 on the first date, similar to previous a systematic review that revealed several Asian, European, and American nations with home-isolation policies (37). In addition, the medical team conducts daily follow-up calls and questionnaires to monitor patient symptoms, including the occurrence of unexpected symptoms and the impact of physical (38), mental, and emotional quarantine (39)(40)(41). Furthermore, this study was strengthened by the large number and variety of Songkhla patients who underwent HI and CI in primary care.…”
Section: Discussionmentioning
confidence: 94%
“…Foremost at risk of experiencing the adverse consequences of the pandemic are children and adolescents who must negotiate their normative developmental tasks against the backdrop of stress and insecurity, which thus compounds their susceptibility and vulnerability (Slone et al, 2022). The widespread global efforts to control the pandemic by confinement, social distancing, school closures, and mass quarantines have dramatically impacted the lives of children and teens who have been forced to remain at home for long periods of time, study remotely, and limit their social interactions with peers.…”
Section: Resilience and Protective Factors During The Pandemicmentioning
confidence: 99%